Analisis Kesiapan Guru dalam Implementasi Asesmen Autentik Pembelajaran Biologi pada Kurikulum Merdeka di SMA Negeri se-Kabupaten Kebumen - Ipah Budi Minarti; Rivanna Citraning Rachmawati; Winda Aulia (Departement of Mathematics Education, 2022)
The teacher is someone who has an important role in implementing authentic assessments and teacher readiness is one of the success factors in implementing authentic assessments. This study aims to determine teacher readiness in implementing authentic Biology learning assessments in the independent curriculum at public high schools in Kebumen Regency, as well as knowing the supporting and inhibiting factors in its implementation. The method used in this research is descriptive qualitative with data collection techniques in the form of interviews and documentation. The sampling technique used is simple random sampling. The data analysis technique used is data reduction, data presentation, and drawing conclusions. The results of the study obtained an average percentage of teacher readiness in implementing authentic Biology learning assessments in the independent curriculum at public high schools in Kebumen Regency based on PAP II, namely 82% in the